Membrane-Interacting Antifungal Peptides - Struyfs, Caroline; Cammue, Bruno P. A.; Thevissen, Karin (Frontiers in Cell and Developmental Biology, 2021)
The incidence of invasive fungal infections is increasing worldwide, resulting in more than 1.6 million deaths every year. Due to growing antifungal drug resistance and the limited number of currently used antimycotics, there is a clear need for novel antifungal strategies. In this context, great potential is attributed to antimicrobial peptides (AMPs) that are part of the innate immune system of organisms. These peptides are known for their broad-spectrum activity that can be directed toward bacteria, fungi, viruses and/or even cancer cells. Some AMPs act via rapid physical disruption of microbial cell membranes at high concentrations causing cell leakage and cell death. However, more complex mechanisms are also observed, such as interaction with specific lipids, production of reactive oxygen species, programmed cell death and autophagy. This review summarizes the structure and mode of action of antifungal AMPs, thereby focusing on their interaction with fungal membranes.